Climate Change and Four Goals for Operational Gaming. (April 2013) - Meadows, Dennis
This foreword highlights the danger of runaway climate change. It outlines four obstacles that appear to prevent world society from adopting a positive approach to climate change: (a) general ignorance about the dynamics of climate change, (b) the long time frame needed for action to produce effective results, (c) the blocking power of the rich and powerful (those with vested interests in greenhouse gas industries), and (d) the ever increasing worldwide demands for energy and resources. Games can be a powerful tool to help developments move in the right direction.